Effects of diacetyl guan-fu base A on pacemaker cells in sinoatrial node of rabbits. - SUN Hua; ZHANG Qing-Zhu; WANG Ru-Bin; JI Jian-Bo (Acta Pharmacologica Sinica, 2016)
AIM: To study the electrophysiological effects of diacetyl guan-fu base A (DGFA) on pacemaker cells in sinoatrial (SA) node. METHODS: Intracellular microelectrode method was used to record parameters of action potential (AP) in SA node of rabbits. RESULTS: DGFA could not only slow down spontaneous firing frequency (SFF), mean rate of repolarization (MRR), and rate of diastolic depolarization (RDD), but also prolong diastolic interval (DI) and duration of action potential (APD) in a concentration-dependent manner in SA node. Furthermore, DGFA markedly decreased the maximum rate of depolarization (MRD) with a slight reduce of the amplitude of action potential (APA) and there was no significant effect on the maximal diastolic potential (MDP). The decrease in SFF caused by DGFA was not affected by atropine (0.05 mg/L). CONCLUSION: The effects might be due to the reduction of calcium influx and potassium efflux, and the muscarinic receptors were not involved.